AUDITS FOR THE MINIMIZATION OF ECO-ANXIETY IN THE WORLD ECONOMY - Nazarova, Karina; Hordopolov, Volodymyr; Nezhyva, Mariia; Mysiuk, Viktoriia; Kopotiienko, Tetiana (UI Scholars Hub, 2020)
The global pandemic of 2019–2020 is changing not only the lives of citizens, but also approaches to business management. The activities of audit companies have not escaped. Problematic and debatable issues need to be addressed to formulate a comprehensive approach to audits in a transformative economic environment and minimize the global economy's eco-anxiety. The purpose of the article is to determine the role of the audit in minimizing the eco-anxiety of the world economy. The study's materials were indicators of the spread of the COVID-19 pandemic in the world, public writings of scientists, official reports of international organizations, regulations, and among other things. COVID-19 has had a negative impact on the economy. Simultaneously, uncertainty in the economies of countries around the world remains, which has implications for reporting organizations and companies providing audit services in Ukraine and around the world. Given the increasing impact of the coronavirus on the global economy and the resulting high uncertainty, conducting a high-quality audit is critical to ensuring that financial statements are properly informed. In many cases, auditors will need to consider the development of alternative auditing procedures to gather sufficient and appropriate evidence. COVID-19 has been a real shock to the global economy. Audits have become an effective tool to minimize the eco-anxiety of the world economy.